Factors Affecting Breast Milk Substitute in Pidie Jaya, Aceh, Indonesia - Frisca Fazira; Nita Arisanti; Dida Gurnida; Hadi Susiarno; Muhammad Alamsyah Azis; Kusnandi Rusmil (Althea Medical Journal)
Background: Breast milk is the first, main, and best natural food for babies. Breast milk contains various nutrients needed in the process of growth and development of babies. Breastfeeding is a health behavior carried out by mothers. This study aimed to analyze the factors that influence the provision of breast milk substitutes.